The walking dead. AMC presents ; Idiot Box ; Skybound ; Circle of Confusion ; Valhalla Entertainment ; AMC Studios ; developed by Frank Darabont ; directed by Rosemary Rodriguez [and others]. [videorecording] / The complete eighth season (2018)
Summary goes here